A thermodynamically consistent model for chemically induced viscoelasticity in covalent adaptive network polymers. (1st December 2022) - Qin, Bao; Zhong, Zheng; Zhang, Tong-Yi
Abstract: Covalent adaptive networks (CANs) can rearrange their network topology via bond exchange reactions (BERs) under external stimuli such as solvent, temperature, pH and light, and are promising in thermoforming, self-healing, reprocessing and recycling applications. For example, BERs trigged by water would exert a great influence on the mechanical behaviors of polyimine CANs by changing their network topology, and vice versa, mechanical stress can make an impact on the kinetics of BERs by accelerating or slowing the transportation of water. This paper aims to present a rigorous thermodynamically consistent model for CANs with diffusion-reaction-deformation coupling behaviors. Thus, a mixture theory-based continuum framework for open systems is developed by choosing the host solid as a reference media, within which the first and second thermodynamic laws for every species inside the host solid are established. Then, the chemically induced stress relaxation is linked with water diffusion and chemical reactions to obtain the dependence of the relaxation time on water concentration and reaction parameters in view of the fact that BERs will break stressed chains and result in new stress-free chains. Finally, the proposed model is verified by comparison of the nonlinear stress-strain relation between model predictions and experimental data of the polyimine CANs at high temperature, and illustrated by simulating the viscoelasticity of a polyimine sample immersed in water and subjected to uniaxial tension. The results reveal that BERs is the dominated cause of the viscoelasticity at high temperature and the diffusive water would also have an important effect on stress relaxation of the polyimine CANs.